Analisis Kesesuaian Wisata Pantai Di Desa Tanjung Kelumpang Kabupaten Belitung Timur - jebri jebri; Kurniawan Salim; Arthur M Farhaby (Akuatik: Jurnal Sumberdaya Perairan, 2023)
East Belitung Regency is one of the regions in the Province of Bangka Belitung Islands that has the potential for tourism, one of which is Punai Beach, Pandan Island Beach and Pengkalan Limau Beach located in Tanjung Kelumpang Village, Simpang Pesak District. Although it is known that the IKW value of the tourism suitability index and its management strategy, therefore the method used in this study uses the purposive sampling method with IKW analysis supported by SWOT analysis. Data collection is carried out by field observations and tourist interviews which are determined based on the LTF (Linear Time Function) formula. The results of this study punai beach has an IKW of 100%, IKW of Pandan Island beach of 87%, IKW of Pengkalan Limau beach of 87% and the results of SWOT analysis have values of x 0.49 and y 0.37 including kuadran I. Punai Beach has parameters that are very suitable to be used as a place of hardening because there are no weaknesses of the measurement that